Peran Modin dalam Mengurangi Dispensasi Kawin di Jember: Kajian Perspektif Maqashid al-Usrah - Muhammad Lutfi Ainun Najib (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2025)
Abstract: Marriage is a fundamental aspect of Islamic teachings aimed at forming a family that embodies Sakinah (tranquility), mawaddah (love), and rahmah (compassion). One of the key requirements to achieve this goal is the physical and psychological maturity of both prospective spouses. However, in Indonesia, particularly in Jember Regency, the rate of early marriage remains high, as evidenced by the increasing number of marriage dispensation requests submitted to the Religious Courts, including in Wuluhan District. A major contributing factor is the lack of maturity and mental readiness among young couples, which often leads to household conflicts and divorce. This study explores the role and strategies of the Modin (a village religious officer) in preventing marriage dispensation cases in Wuluhan District, Jember Regency, through the lens of maqashid al-usrah (family objectives) in Islamic jurisprudence as conceptualized by Jamaluddin Athiyah. Although modin is no longer formally included in the village governmental structure, their presence is still highly recognized by the community, especially in religious and social affairs, including marriage. In practice, modin actively engages in public education, counseling, mediation, and collaboration with village officials and community leaders to discourage early marriage. This study emphasizes that modin plays a strategic role in reducing early marriage rates by disseminating awareness about the negative consequences of underage marriage and the importance of maturity in building a household. The maqashid al-usrah framework highlights the importance of marriage in preserving lineage, ensuring financial stability, fostering religious values, and achieving overall family well-being. Therefore, optimizing the role of modin is highly relevant as a concrete effort to realize quality families and prevent the adverse impacts of child marriage. Keywords: Early Marriage, Marriage Dispensation, Modin, Maqashid al-Usrah, Wuluhan District, Jamaluddin Athiyah. Abstrak: Pernikahan merupakan bagian penting dalam ajaran Islam yang bertujuan membentuk keluarga yang sakinah, mawaddah, wa rahmah. Salah satu syarat tercapainya tujuan tersebut adalah kedewasaan calon suami dan istri, baik secara fisik maupun psikis. Namun, di Indonesia, khususnya di Kabupaten Jember, angka pernikahan dini masih tinggi, terbukti dari banyaknya pengajuan dispensasi kawin ke Pengadilan Agama, termasuk di Kecamatan Wuluhan. Salah satu faktor pendorongnya adalah kurangnya kedewasaan dan kesiapan mental para pelaku nikah dini, yang kemudian berujung pada konflik rumah tangga dan perceraian. Penelitian ini mengkaji peran dan strategi Modin dalam mencegah terjadinya dispensasi kawin di Kecamatan Wuluhan, Kabupaten Jember, dengan pendekatan maqashid alusrah dalam maqashid syariah menurut Jamaluddin Athiyah. Modin, meskipun secara struktural tidak tercantum dalam organisasi pemerintahan desa, tetap diakui masyarakat sebagai tokoh penting dalam urusan keagamaan dan sosial, termasuk pernikahan. Dalam praktiknya, modin berperan aktif memberikan pembinaan, sosialisasi, mediasi, hingga melibatkan tokoh masyarakat demi mencegah pernikahan dini. Penelitian ini menekankan bahwa modin memiliki peran strategis dalam upaya menurunkan angka pernikahan dini dengan cara mensosialisasikan risiko-risiko negatif pernikahan usia muda dan pentingnya kedewasaan dalam pernikahan. Pendekatan maqashid al-usrah menegaskan pentingnya pernikahan sebagai sarana menjaga keturunan, nasab, keuangan keluarga, dan nilai-nilai keberagamaan. Maka dari itu, optimalisasi peran modin sangat relevan sebagai upaya nyata mewujudkan keluarga yang berkualitas dan terhindar dari berbagai dampak negatif pernikahan dini. Kata Kunci: Pernikahan Dini, Dispensasi Kawin, Modin, Maqashid al-Usrah, KecamatanWuluhan, Jamaluddin Athiyah.